Single and multi-user virtual patient design in the virtual world - Taylor,D; Patel,V; Cohen,D; Aggarwal,R; Kerr,K; Sevdalis,N; Batrick,N; Darzi,A (Studies in Health Technology and Informatics, 2011)
This research addresses the need for the flexible creation of immersive clinical training simulations for multiple interacting participants and virtual patients by using scalable open source virtual world technologies. Initial development of single-user surgical virtual patients has been followed by that of multi-user multiple casualties in a field environment and an acute hospital emergency department. The authors aim to validate and extend their reproducible framework for eventual application of virtual worlds to whole hospital major incident response simulation and to multi-agency, pan-geographic mass casualty exercises.